Combustion improvement in HCCI engine operating on synthesis gas via addition of ozone or excited oxygen molecules to the charge: Modeling study. (13th April 2017) - Starik, A.M.; Korobov, A.N.; Titova, N.S.
Abstract: Comprehensive analysis of the possibility of the improvement of combustion and reduction of NO and CO emissions for HCCI engine operating on syngas–air mixture through the production in the intake charge highly reactive species, such as singlet delta oxygen O2 ( a 1 Δg ) or ozone molecules, is conducted. The computations with the usage of detailed reaction mechanism of syngas oxidation, involving the reactions with O2 ( a 1 Δg ) and O3 molecules, have showed that the abundance of O2 ( a 1 Δg ) or O3 molecules in the charge accelerated the ignition and made it possible to increase slightly the mass specific energy released during HCCI combustion and to reduce simultaneously the NO and CO emissions both at nominal and at low load regimes. Moreover, the production of O2 ( a 1 Δg ) or O3 molecules in the charge even in a small amount allows one to extend the range of stable combustion toward the extremely fuel–lean mixture and ensure the stable operation of HCCI engine at low load. The advance in the energy released during combustion due to the presence of O2 ( a 1 Δg ) or O3 in the charge is substantially greater the energy needed for the production of O2 ( a 1 Δg ) and O3 molecules. Highlights: Simulation of combustion and emission characteristics of HCCI engine is conducted. Syngas is considered as a fuel. The effect of the addition of O3 or O2 ( a 1 Δg ) molecules to the intake charge on combustion is analyzed. The production of such molecules ensures the stable operation of engine at low load. Simultaneously, the emission of NO and CO decreases in this case.